Efectos de diferentes densidades de siembra en la cría de alevines de tilapia roja (Oreochromis mossambicus x O. niloticus) en tanques - Benavides Toral, Ronald Octavio (2022)
The research work was carried out at the Aquaculture Facility of the Faculty of Agricultural Sciences, on the grounds of the experimental farm ``La María´´, owned by the State Technical University of Quevedo, located at Kilometer 7 ½ of the Quevedo - El Empalme, entrance to the Mocache canton, Los Ríos province, with the objective of determining the effect of four stocking densities on the rearing of red tilapia fingerlings (Oreochromis mossambicus x O. niloticus) in tanks. For this, 500 fingerlings of (Oreochromis mossambicus x O. niloticus) were used in the growth phase with 5.00 ± 1.5 g of live weight, which were distributed in a Completely Random Design with four treatments and four repetitions and each experimental unit with 50, 100, 150, 200 fish/m3, generating treatments t1, t2, t3, t4, respectively. The results of the cultured fish with a density of 50 fish/m3 presented better growth rate in weight, food conversion, and survival with 2.9 g/day, 1.2 and 100%; representatively, meanwhile, the cultured fish with densities of 50 and 100 fish/m3 showed better biomass and less water consumption, each change of water was every 7 days for the density of 50 fish/m3 and 6 days for the density of 100 fish/m3. In conclusion, seeding densities influence the biological responses of (Oreochromis mossambicus x O. niloticus); lower densities report better responses to biometric parameters.